Three new C21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases. Issue 8 (18th April 2022) - Wang, Xu; Ma, Qing-Yun; Liu, Chen; Yang, Jia; Lv, Qing-Tao; Tian, Zhen-Hua; Jiang, Hai-Qiang; Rong, Rong
Abstract: Three new steroidal glycosides, metapregnoside A–C (II –IV ), together with one known compound, byzantionoside B (I ), were isolated from the fresh whole herb of Metaplexis japonica by using high-speed countercurrent chromatography and semi-preparative liquid chromatography. Their structures and relative configurations were elucidated by spectroscopic methods including 1D NMR, 2D NMR and HR-ESI-MS. The potential targets of compound I –IV were identified by virtual screening. And the potential inhibitory effects of these compounds on tyrosine protein kinases were compared by molecular docking. Byzantionoside B (I ) was the first isolated compound from Metaplexis genus. The docking score of metapregnoside C (IV ) was the highest. And the sugar chain residues at position C-20 in the pregn-4-en-3-one derivatives is the main factor affecting their docking scores on tyrosine protein kinases Fes/Fps. Graphical Abstract: